Effect Of Ozone Washing On Physicochemical Properties And Gel Strength Of Surimi Made From African Catfish (Clarias Gariepinus) - Bakar, Nur Aisyah Munirah Abu (Universiti Sains Malaysia, 2020)
Ozone (